An Otischalkian dinosauromorph assemblage from the Los Esteros Member (Santa Rosa Formation) of New Mexico and its implications for biochronology and lagerpetid body size. Issue 1 (2nd January 2020) - Beyl, Alexander; Nesbitt, Sterling; Stocker, Michelle R.
ABSTRACT: The strata of the American Southwest, particularly the Chinle Formation and the Dockum Group, are critical to our understanding of faunal diversity and evolution in the Late Triassic. In recent decades, these strata have informed the evolution of close dinosaur relatives, which remain poorly sampled and enigmatic in their geographic distribution. Here, we describe and discuss a new non-dinosaurian dinosauromorph assemblage from the Los Esteros Member of the Santa Rosa Formation at the base of the Dockum Group in east-central New Mexico. This assemblage includes hindlimb fragments assignable to Silesauridae and Lagerpetidae. Much of the lagerpetid material, assignable to Dromomeron, is of unusually large size. Based on a dataset of complete lagerpetid femora, we estimate a total femoral length of 221.9 mm for one partial femur, making it the largest reported individual. We also provide biochronological support that at least a portion of the Los Esteros Member corresponds to the Otischalkian land vertebrate faunachron through the identification of non-Mystriosuchinae phytosaurs. Subsequently, we question the presence of a bifurcated lateral ridge on the squamosal of all phytosaurs currently assigned to Parasuchus . This is the first Otischalkian fauna identified from New Mexico, and it reveals lagerpetids achieved large body size earlier than previously recognized. Our identifications expand the geographic and temporal range of non-dinosaurian dinosauromorphs in the American Southwest. The material presented here, in conjunction with an increasing number of Dromomeron specimens, demonstrates that non-dinosauriform dinosauromorphs could match or exceed the body size of many coeval dinosaurs.